2013
DOI: 10.5402/2013/623936
|View full text |Cite
|
Sign up to set email alerts
|

Routine Duodenal Biopsies in the Absence of Endoscopic Markers of Celiac Disease Are Not Useful: An Observational Study

Abstract: Background. European studies have shown the utility of limiting endoscopic biopsies to diagnose celiac disease (CD) to patients that have high-risk symptoms or present with positive serology. However, many centers in the U.S. have open access endoscopy. Patients are referred without prior serologic testing, and endoscopists often decide whether or not to biopsy at the time of procedure. Aims. Evaluate the yield of duodenal biopsies for the diagnosis of CD in patients undergoing upper endoscopy without prior se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Earlier studies by Balasubramanian P et al (14) reported normal villi architecture in 40.6% cases. Endoscopic duodenal nodularity was found in 16.6% cases in our study which are quite similar to study conducted by Castro F et al [16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Earlier studies by Balasubramanian P et al (14) reported normal villi architecture in 40.6% cases. Endoscopic duodenal nodularity was found in 16.6% cases in our study which are quite similar to study conducted by Castro F et al [16].…”
Section: Discussionsupporting
confidence: 91%
“…(14) Major histopathological features of untreated celiac disease in duodenal biopsies are intraepithelial lymphocytosis, increased number of inflammatory cells at lamina propria and villous atrophy [15]. Howeverdiagnostic yield of routine duodenal biopsy for celiac disease was low as reported by Castro F et al, Stoven SA et al [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the poor diagnostic yield (0.4–1.6%) of routine SBBx in the evaluation of anemia without positive serological tests or other strong indications . These studies have established the need for biopsies in only those with “high‐risk” features but have not categorized anemia into IDA versus non‐IDA, a group in which the incidence of celiac disease is low.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, routine duodenal or small bowel mucosal biopsies (SBBx) are recommended for patients presenting with anemia. However, previous studies have demonstrated the poor diagnostic yield of routine SBBx, at a significant cost to the health‐care system . Whilst SBBx is generally safe, clinically significant bleeding requiring blood transfusion can occur in 0.004–0.14%, and there are case reports of SBBx‐associated perforation …”
Section: Introductionmentioning
confidence: 99%
“…Careful examination of the duodenum is needed to detect endoscopic markers of villous atrophy, which should trigger the endoscopist to do biopsies. As shown by Castro et al, detection of endoscopic markers is associated with a high probability of diagnosing celiac disease (15.6 positive likelihood ratio) [87], so they should be attentively searched for, especially in high-risk patients.…”
Section: Endoscopic Markers In Celiac Diseasementioning
confidence: 99%